1969
DOI: 10.1029/wr005i001p00048
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Waters From Playas on the Southern High Plains

Abstract: An estimated 2.5 to 3.0 million acre-feet of runoff water accumulate annually in playas on the Southern High Plains. This large water resource should be developed for more intensive use; however, past lack of knowledge about its quality has impeded progress. Thirteen playas were sampled over an area extending about 100 miles from northeast to southwest and covering two major soil types. The water from playas contained less salts than ground water and was of excellent quality for irrigation. Nitrate contents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Montana. However, long term gauging records and estimations Lotspeich et al (1969) found that runoff water in playas in from short term records indicate an average runoff of only 2.5 the Southern High Plains was less saline than ground water and cm per year in the area (Earl L. Neff, personal communication).…”
mentioning
confidence: 99%
“…Montana. However, long term gauging records and estimations Lotspeich et al (1969) found that runoff water in playas in from short term records indicate an average runoff of only 2.5 the Southern High Plains was less saline than ground water and cm per year in the area (Earl L. Neff, personal communication).…”
mentioning
confidence: 99%